PPU campus - Al-Jabary, Yousif; Al-Sadi, Mansor; Mahmoud, Zaher; Ersheid, Ayman (جامعة بوليتكنك فلسطين - مباني, 2010)
The main goal of this project is to design the library building after determining its location on campus of PPU in two sides architectural and structural side to execute that in the stage one of construction of the campus. In this project there are seven chapters to satisfy all aims of the project chapter one is an introduction that gives us guidelines for the project while chapter two and three are for campus design in analytical and architectural studies. The other chapters are divided into two main sides, architectural and structural for the library design building. In the architectural design , the side of the library was determined according to the site of campus . the architectural drawings were prepared after studying all of the architectural requirements for all parts of library areas. In the structural design, a structural study was made to determine what members to design and all structural reqirements that must be considerd in this project. The structural analysis were calculated at the end according to the ACI code for all of the structural members from roof to footings. Then structural drawing were prepared to illustrate the distribution of steel in structural members.
no of pages 390 , 25281, مباني 12/2010, in the store
Keywords: campus